Superconductivity of topological insulator Bi2Se3 - Mykytiuk, Mykhailo; Druzhinin, Anatoly; Ostrovskii, Ihor; Liakh‑Kaguy, Natalia (Physics and Chemistry of Solid State, 2026)
The present paper deals with investigation of magnetoresistance and temperature dependencies of resistance for Pd-doped Bi2Se3 whiskers. The samples with palladium doping concentration of (1 ÷ 2) × 1019 cm−3 were studied in the temperature range of 1.5 ÷ 77 K and magnetic field induction up to 1.5 T. A sharp drop in the whisker resistance was found at the temperature of 5.3 K and 2.2 K. This effect can be explained as a contribution of superconductivity at temperatures under 5.3 K. Low temperatures magnetoresistance investigations allow to obtain critical magnetic field for the superconductivity of about 1.5 T.